How we fight : crusades, quagmires, and the American way of war - Tierney, Dominic, 1977- (New York : Little, Brown and Co., 2010)
Examines military conflicts from the Civil War to the present to explore the opposing mindsets that drive Americans to support wars that defend democracy and overthrow tyrants while resisting the necessary work of nation building.
For liberty and vengeance : the crusade tradition -- Through a glass, darkly : the quagmire tradition -- Birth of a nation -- Heel of Achilles -- To end all war -- When the saints go marching in -- Black gold and black hawks -- The Bush warriors -- The founding tradition.
Includes bibliographical references (p. 305-329) and index.
Keywords: War -- Public opinion; Public opinion -- United States; National characteristics, American; United States -- History, Military